2020
DOI: 10.3389/fphys.2020.00124
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Progression of Diabetic Cardiomyopathy in a Mouse Model of Type 1 Diabetes

Abstract: Integrative Physiology, a section of the journal Frontiers in PhysiologyThe incidence of diabetes and its association with increased cardiovascular disease risk represents a major health issue worldwide. Diabetes-induced hyperglycemia is implicated as a central driver of responses in the diabetic heart such as cardiomyocyte hypertrophy, fibrosis, and oxidative stress, termed diabetic cardiomyopathy. The onset of these responses in the setting of diabetes has not been studied to date. This study aimed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…KLK8 -/- mice exhibited significantly smaller left ventricular end-diastolic and end-systolic dimension and higher fractional shortening and ejection fraction than KLK8 +/+ mice (Figure 2 G, Table 2 ). Cardiac fibrosis is closely associated with cardiac diastolic dysfunction 21 , 22 . The present study next observed the effect of KLK8 deficiency on diabetes-induced diastolic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…KLK8 -/- mice exhibited significantly smaller left ventricular end-diastolic and end-systolic dimension and higher fractional shortening and ejection fraction than KLK8 +/+ mice (Figure 2 G, Table 2 ). Cardiac fibrosis is closely associated with cardiac diastolic dysfunction 21 , 22 . The present study next observed the effect of KLK8 deficiency on diabetes-induced diastolic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain measures of LV function, echocardiography was performed in anaesthetised mice (ketamine/xylazine/atropine: 80/8/0.96 mg/kg i.p.) at study endpoint utilising a Philips iE33 ultrasound (North Ryde, NSW, Australia) with 15 MHz linear (M-mode) and 12 MHz sector (Doppler) transducer, as previously described (Prakoso et al, 2017;Tate et al, 2019;De Blasio et al, 2020;Prakoso et al, 2020;Prakoso et al, 2021a). LV chamber dimensions and fractional shortening were assessed from M-mode imaging.…”
Section: Echocardiographymentioning
confidence: 99%
“…LV chamber dimensions and fractional shortening were assessed from M-mode imaging. LV filling was assessed using transmitral Doppler; the ratio of early (E) and late (A) peak blood flow velocities (E/A ratio), deceleration time and IVRT were measured (Prakoso et al, 2017;Tate et al, 2019;De Blasio et al, 2020;Prakoso et al, 2020;Prakoso et al, 2021a).…”
Section: Echocardiographymentioning
confidence: 99%
See 2 more Smart Citations